Pengaruh Cahaya Terhadap Pertumbuhan Tanaman - Marta Tristanti Mendrofa; Berkat Jaya Gulo; Serlin Jessica Mendrofa; Andi Donal Putra Zebua; Putri Harta Bawamenewi; Apriani Hia (Jurnal Ilmu Pertanian dan Perikanan, 2026)
This study aims to examine the differences in plant growth placed in bright and dark places. Light is one of the important factors in photosynthesis, which plays a direct role in plant growth and development. In this study, several plant samples from the same species were grown in controlled environmental conditions and placed in two different locations: a bright place with direct access to sunlight, and a dark place that did not receive any light at all. The parameters measured included plant height, number of leaves, and leaf color during a certain period. The results showed that plants placed in bright places had more optimal growth than plants in dark places. Plants in bright places showed a significant increase in height, a greater number of leaves, and fresh green leaf color. In contrast, plants in dark places tended to have stunted growth with pale or yellowish leaf color. This study confirms the importance of light as a key factor in plant growth, and provides insight into plant management in various environmental conditions.